Role of tumour necrosis factor-alpha (TNF-α) in the induction of HIV-1 gp120-mediated CD4(+) T cell anergy - KANEKO, H (Blackwell Science Inc, 1997)
The HIV-1 envelope glycoprotein (gp120) is known to induce antigen-specific and non-specific CD4(+) T cell anergy. We found that early T cell activation, as indicated by HLA-DP expression in the early G(1) (G(1A)) phase of the cell cycle, and the inhibition of mitogen-mediated IL-2 production induced by gp120, required TNF-α produced by gp120-stimulated macrophages. In the presence of an antibody to TNF-α, these changes induced by gp120 were inhibited, while recombinant TNF-α induced similar abnormalities of CD4(+) T cells, even in the absence of gp120. On the other hand, inhibition of the mixed lymphocyte reaction (MLR) in CD4(+) T cells by gp120, which may be related to gp120-mediated down-regulation of CD4 expression on T cells and activation of protein tyrosine kinase p56(lck) in CD4(+) T cells, was observed even in the absence of macrophage-derived TNF-α induced by gp120. These observations indicate that both TNF-α-dependent and independent events contribute to gp120-mediated CD4(+) T cell anergy, and TNF-α appears to play an important role in inducing CD4(+) T cell anergy in HIV-1 infection.